Implementation of Musyarakah Financing in BMT Al-Munawarah - Setya Nugroho Isri Yuwono; Jaharuddin Jaharuddin (BASKARA : Journal of Business and Entrepreneurship, 2023)
This study aims to determine the application and conformity of the sharia musharakah contract with the DSN fatwa at Baitul Maal wa Tamwil (BMT) Al-Munawwarah, using a qualitative case study approach. The data used in this study used primary and secondary data by conducting direct interviews with branch managers, tellers, and customers at BMT and searching for data sources in journals, books, and literature. The results of this study explain that BMT has several savings products and financing products in it for customer needs. In conducting Musyarakah financing, customers need to fill out a form and complete the requirements set by the BMT. In its implementation, BMT Al-Munawwarah has run musharakah financing following the DSN-MUI Fatwa with the principle of profit sharing. The ratios that are usually used for BMT are 50%: 50%, 60%: 40%, and 70%: 30%. The marketing strategy used by BMT in marketing its financing products is through print media such as brochures, and banners